Analysing and Investigating Performance Metrics of Supply Chains: A Case Study on Alcohol and Liquor Industriesl - Dagne Birhanu; Lanka Krishnanand; A. Neelakanteswara Rao (International Journal of Supply Chain Management, 2014)
Identifying the proper supply chain practices and metrics is highly essential to check and balance the normal health condition of any organization. This paper deals with the possible qualitative supply chain practices and metrics which are tested on 5 Ethiopian Alcohol and Liquor manufacturing supply chains. The practices and metrics are derived from literatures made by the authors. To further clarify the supply chain metrics, questionnaire is designed and distributed to different levels of managers of the companies to formulate hypothesis. Using the right metrics, the significance of hypothesis is tested using SPSS 16.0 and MINITAB 16.1 software. For item reliability, Cronbachs alpha test was calculated to all items arranged in a five point Likert scale, and the test result shows the reliability of the items. The results in between groups and within groups are compared using analysis of variances. The results show that the majority of the practices and metrics the companies differ among and within the companies and concluded that the supply chain practices and metrics are not uniform in Ethiopian supply chains.